1999
DOI: 10.1097/00042560-199901010-00009
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 Subtypes Among Blood Donors From Rio de Janeiro, Brazil

Abstract: The prevalence of HIV infection in Brazil is one of the highest in the world. In addition, transfusion-transmitted HIV accounts for 2.3% of all AIDS cases in Brazil. The objective of this study was to evaluate genetic diversity and distribution of HIV-1 strains circulating in the blood-donor population. We characterized 43 seropositive blood units collected from volunteer blood donors residing throughout Rio de Janeiro, Brazil. Viral RNA was extracted from plasma, reverse transcribed, and amplified by nested p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
52
1
5

Year Published

2000
2000
2010
2010

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 65 publications
(65 citation statements)
references
References 11 publications
7
52
1
5
Order By: Relevance
“…This result is also in agreement with the distribution of HIV-1 subtypes in Brazil, where non-B virus strains are frequently found and those from clade F are the second most prevalent one (18%). Mosaics B/F, B/C, and B/D have also been reported in our country (6,26,31).…”
Section: Discussionsupporting
confidence: 71%
“…This result is also in agreement with the distribution of HIV-1 subtypes in Brazil, where non-B virus strains are frequently found and those from clade F are the second most prevalent one (18%). Mosaics B/F, B/C, and B/D have also been reported in our country (6,26,31).…”
Section: Discussionsupporting
confidence: 71%
“…The M (main) group, the widest spread, has been further subdivided into at least nine subtypes (A-D, F-H, J, and K) and 32 circulating recombinant forms (CRF), whereas a high diversity of unique intersubtype recombinant forms has also been demonstrated (Leitner et al 2005). In Brazil, molecular analyses of HIV-1 nucleotide sequences have shown an epidemic driven mainly by three group M subtypes: B, C, and subsubtype F1 (heretofore designated subtype F1), as well as a myriad of unique BF1 intersubtype recombinants (Morgado et al 1998, Tanuri et al 1999, Vicente et al 2000, Soares et al 2003. Isolated cases of other subtypes, such as subtype D (Morgado et al 1998, CoutoFernandez et al 2006), subtype A (Caride et al 2000, CRF02_AG (Pires et al 2004, Couto-Fernandez et al 2005), CRF28_BF and CRF29_BF (De Sa Filho et al 2006 have also been reported.…”
mentioning
confidence: 99%
“…There are also B/F, B/C, and B/D mosaics (20,23,26). The prevalence of circulating drug-resistant strains of virus in Brazil has been reported only for drug-naive and treated adults (3,5,6,27).…”
mentioning
confidence: 99%